2007
DOI: 10.1186/1478-4491-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Strategic management of the health workforce in developing countries: what have we learned?

Abstract: The study of the health workforce has gained in prominence in recent years, as the dynamic interconnections between human resource issues and health system effectiveness have come into sharper focus. This paper reviews lessons relating to strategic management challenges emerging from the growing literature in this area. Workforce issues are strategic: they affect overall system performance as well as the feasibility and sustainability of health reforms. Viewing workforce issues strategically forces health auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
28

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 39 publications
3
82
0
28
Order By: Relevance
“…This study has identified and prioritized these factors under similar parameters of suitability of their implementation with possible revision of the HRH policies in Pakistan (Table 2). While other studies have generally focused on organizational context and physicians' individual attributes, 13,14 this study explored beyond this paradigm and identified the linkages between these and other attributes to develop a conceptual framework that would form basis for further research. In addition, the study also identified factors around organizational and external environment by focusing on the three tiers of the system namely, service providers (physicians), district level management and provincial and policy level participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has identified and prioritized these factors under similar parameters of suitability of their implementation with possible revision of the HRH policies in Pakistan (Table 2). While other studies have generally focused on organizational context and physicians' individual attributes, 13,14 this study explored beyond this paradigm and identified the linkages between these and other attributes to develop a conceptual framework that would form basis for further research. In addition, the study also identified factors around organizational and external environment by focusing on the three tiers of the system namely, service providers (physicians), district level management and provincial and policy level participants.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that a set of financial and non-financial factors affect motivation of health staff at primary healthcare (PHC) facilities. Work compensation ensures professional survival and security of individuals 14 ; remuneration, appropriate with the relevant market, ensures staff retention in developing countries. 15 However, financial incentives are important for motivation of workforce but are not the only factor responsible for the lack of motivation.…”
Section: Introductionmentioning
confidence: 99%
“…This chapter is not a comprehensive review of management of health workers in Africa. For that, see, for example, Fritzen (2007) and Egger and others (2005). Our perspective is more focused.…”
Section: Notesmentioning
confidence: 99%
“…It has in fact been reported that nurses value more hospital nursing practice than community health nursing. [6][7][8] Presently in Nigeria many nurses who accept postings to rural areas prefer to live in nearby urban centres and shuttle between the urban centres and the rural location of their professional assignment. This shuttling may affect their regularity, punctuality and commitment to work and consequently their work output.…”
Section: Introductionmentioning
confidence: 99%